Modulation Processes and Mathematical Models of the TCR - Ioannou, Stelios; Argyrou, Maria C.; Christodoulides, Paul; Raspopoulos, Marios; Darwish, Mohamed; Marouchos, Christos (My University, 2021)
This work presents an in-depth analysis, identifies and derives the modulation processes in the Thyristor controlled Reactor by applying the Switching Function technique. The basic expressions of the circuit for current and voltage are derived as a function of the Switching Function. Hence the steady state analysis is performed, and the large signal mathematical models are derived. The model has the advantage of incorporating both the switching action of the thyristors and its triggering behaviour. Such a model can be used to investigate the current harmonics in a dynamic environment. Furthermore, the derived model is verified using the PSIM simulation software. The mathematical model results and the circuit simulation results are both analysed and discussed. As the results show, the proposed mathematical model correctly predicts the order and magnitude of the current harmonics with minimal error; less than 0.4% up to the fifth harmonic. Finally, it is worth noting that the switching function mathematical model is simple and its speed of execution is improved significantly by investigating specific range of harmonics.
Keywords: Mathematical Modelling; PSIM Simulations; Thyristor; TCR; Modulation Processes